PERAN TAFSIR KONTEMPORER BAGI UMAT MODERN - Najib, M. Miftahun (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
: This study entitled "Facing Challenges: The Role of Contemporary Interpretation for Modern People" aims to analyze the characteristics and relevance of contemporary interpretation in answering various problems faced by modern people. First, this study shows that contemporary interpretation has more diverse characteristics compared to classical interpretation, allowing for more adaptive interpretations to the current social and cultural context. Second, this study emphasizes that contemporary interpretation is still very relevant and able to provide answers to the challenges that arise due to advances in information technology, which have changed people's lifestyles and created new problems in various aspects of life. The background of this problem is important because complex challenges require solutions so that humanity, especially Muslims, can live in harmony. By analyzing the works of scholars and interpreters in the contemporary era, this study seeks to provide a deeper understanding of the contribution of contemporary interpretation in facing the challenges of the times. Keywords: Contemporary Interpretation, Solutions, Modern People